2017
DOI: 10.1111/acer.13300
|View full text |Cite
|
Sign up to set email alerts
|

Cellular GABAergic Neuroactive Steroid (3α,5α)‐3‐Hydroxy‐Pregnan‐20‐One (3α,5α‐THP) Immunostaining Levels Are Increased in the Ventral Tegmental Area of Human Alcohol Use Disorder Patients: A Postmortem Study

Abstract: Background The GABAergic neuroactive steroid (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP, allopregnanolone) enhances GABAergic activity and produces subjective effects similar to ethanol. The effect of chronic alcohol exposure on 3α,5α-THP concentrations has been studied in mouse, rat, and monkey limbic brain areas. Chronic ethanol exposure produced divergent brain region and cell specific changes in 3α,5α-THP concentrations in animal studies. However, 3α,5α-THP levels in similar human brain regions have never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…However, in the same subjects allopregnanolone immunoreactivity in the hippocampus was slightly enhanced (Beattie et al, ), suggesting that chronic alcohol may selectively dysregulate GABAergic neuroactive steroids across the brain regions. Likewise, increased allopregnanolone immunoreactivity was reported in the VTA and substantia nigra pars medialis of male human alcoholics (Hasirci et al, ). Furthermore, the neuroactive steroid precursors pregnenolone and dehydroepiandrosterone were elevated in several limbic regions of alcohol‐dependent male and female subjects (Karkkainen et al, ).…”
Section: Allopregnanolone And/or Pregnenolone May Protect Individualsmentioning
confidence: 82%
“…However, in the same subjects allopregnanolone immunoreactivity in the hippocampus was slightly enhanced (Beattie et al, ), suggesting that chronic alcohol may selectively dysregulate GABAergic neuroactive steroids across the brain regions. Likewise, increased allopregnanolone immunoreactivity was reported in the VTA and substantia nigra pars medialis of male human alcoholics (Hasirci et al, ). Furthermore, the neuroactive steroid precursors pregnenolone and dehydroepiandrosterone were elevated in several limbic regions of alcohol‐dependent male and female subjects (Karkkainen et al, ).…”
Section: Allopregnanolone And/or Pregnenolone May Protect Individualsmentioning
confidence: 82%
“…It is known that different alcohol administration paradigms or durations can produce different withdrawal‐induced alterations (Knapp and Breese, ; Lopez and Becker, ), including different shifts in GABA A receptor subunit gene expression (Matthews et al., ). Alteration of sensitivity to GABA could occur through other mechanisms, including decreased production of allopregnanolone (Beattie et al., ; Hasirci et al., ; Maldonado‐Devincci et al., ), redox modulation (Calvo and Beltran Gonzalez, ), or regulation of synthesis, transport, or degradation of GABA (Roth and Draguhn, ). Withdrawal‐induced alteration of processes (e.g., allopregnanolone synthesis) in other types of cells (e.g., astrocytes or microglia) within the VTA could result in a decrease in GABAergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal‐induced alteration of processes (e.g., allopregnanolone synthesis) in other types of cells (e.g., astrocytes or microglia) within the VTA could result in a decrease in GABAergic neurotransmission. It should be noted that increases in allopregnanolone levels were observed in the VTA of human alcoholics (Hasirci et al., ), but no difference in allopregnanolone was observed in the VTA between controls and alcohol‐exposed mice (Maldonado‐Devincci et al., ). The reversal of GABA hyposensitivity by SAHA and changes in HDAC2 and acH3K9 associated with withdrawal would be consistent with a more condensed chromatin during withdrawal and a decrease in mRNA expression of some of the factors increasing GABA sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Many neuroimaging studies refer to the VTA as the entire region, defined by its location with respect to landmark structures (Ballard et al, 2011;Barry et al, 2013;D'Ardenne et al, 2008;Eapen and Gore, 2009;Murty et al, 2014), whilst others, mainly cytoarchitecture studies, distinguish between the arrangement of neural populations of the overall VTA and refer to its components as anatomically distinct nuclei (see Fig. 1; Ding et al, 2016;Hall et al, 2014;Hasirci et al, 2017;Mai et al, 2016;McRitchie et al, 1996;Morales and Margolis, 2017;Paxinos et al, 2012). This lack in agreement in VTA nomenclature was already present in early cytological studies (Halliday and T€ ork, 1986;McRitchie et al, 1996;Swanson, 1982) and this issue remains unsolved (see Fig.…”
Section: Vta Terminologymentioning
confidence: 99%
“…However, although evidence for the SNc as an anatomical and functionally defined region is rather consistent, for the VTA the picture is much more divergent. For example, at the anatomical level, different terminology and definitions exist (Ding et al, 2016;Hall et al, 2014;Halliday and T€ ork, 1986;Hasirci, Maldonado-Devincci, Beattie, O'Buckley and Morrow, 2017;Mai et al, 2016;McRitchie et al, 1996;Morales and Margolis, 2017;Swanson, 1982). In addition, recent data revealed that neural transmission, in the VTA especially, is not restricted to DA alone (Morales and Margolis, 2017;Root et al, 2016) and that it is functionally involved in more than just DA-related behavior.…”
Section: Introductionmentioning
confidence: 99%